2013
DOI: 10.1007/s10646-013-1080-y
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide exposure impacts not only hatching of dormant eggs, but also hatchling survival and performance in the water flea Daphnia magna

Abstract: Laboratory ecotoxicity tests and biomonitoring in aquatic systems are currently based on the active component of invertebrate communities. Even though dormant egg banks are crucial for the long term survival and community dynamics of many aquatic organisms, the effects of anthropogenic activities on dormant egg bank dynamics have rarely been studied. In this study we investigated the effects of two pesticides with a different mode of action (carbaryl and fenoxycarb) on hatching of Daphnia magna dormant eggs (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 72 publications
(84 reference statements)
2
40
0
Order By: Relevance
“…Previously, effects of pesticides and sedimentary metals have been observed on development and hatching success of the diapausing eggs of cladocerans Daphnia (Navis et al 2013(Navis et al , 2015Rogalski 2015). Additionally, a field study showed metals were accumulated by Daphnia ephippia (Wyn et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, effects of pesticides and sedimentary metals have been observed on development and hatching success of the diapausing eggs of cladocerans Daphnia (Navis et al 2013(Navis et al , 2015Rogalski 2015). Additionally, a field study showed metals were accumulated by Daphnia ephippia (Wyn et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, because only the asexual portion of the life cycle is commonly investigated in toxicity studies, the true vulnerability of zooplankton to toxicants is often underestimated (Preston and Snell 2001;Navis et al 2015). Several studies assessed the effects of pesticides, heavy metals, and endocrine-disrupting chemicals on sexual reproductive parameters of rotifers (Snell and Carmona 1995;Preston et al 2000;Yoshinaga et al 2000;Preston and Snell 2001;Radix et al 2002;Marcial et al 2005;Ríos-Arana et al 2007) and cladocerans (Tatarazako and Oda 2007;Navis et al 2013Navis et al , 2015. Their results showed that, depending on the species and contaminants tested, reproductive parameters such as mixis ratio (i.e., proportion of sexual females relative to all females, sexual and asexual) and fertilization, and diapause parameters such as resting egg production and resting egg hatchability are among the most sensitive endpoints to assess toxicity in zooplankton species.…”
Section: Introductionmentioning
confidence: 99%
“…Because these eggs are immobile, and only require a steady flow of oxygenated water to survive, they are a perfect candidate for this single pump flow cell system. Resting eggs are of considerable importance as they exhibit different responses to toxins compared with adults and juveniles . Resting egg banks are critical to a species survival, and if they are compromised by a toxin, it can potentially lead to an ecosystem collapse, especially if the organism is a keystone species like Daphnia , connecting the producers (plants) to the consumers (higher animals) in the food web.…”
Section: Flow Cell Designmentioning
confidence: 99%
“…Moreover, the egg bank also represents a storage of genetic variation produced by sexual recombination over several generations [3,54,55], and altered hatching dynamics from the sediments may have severe implications on the evolutionary potential of species [3]. In contrast to the small number of ecotoxicological studies on egg banks conducted to date, which generally found detrimental effects on hatching success and hatchling fitness [17], the present study reveals a novel result: a significant increase in hatching success of resting eggs when exposed to organic contaminants. Daphnia resting eggs do not all hatch at the same occasion [56], which allows for transgenerational overlap and reduces the risk of extinction [4,54].…”
Section: Discussionmentioning
confidence: 99%